Ontologi: Memahami Hakikat Realitas dan Aplikasinya dalam Ilmu Akuntansi - Pransida Budaya; Riduan Riduan; Darwin Effendi; Zainul Rifqi; Arianda Pratama (Journal Innovation In Education, 2025)
This article comprehensively reviews the definition of ontology as a branch of philosophy that studies the nature of existence or reality. Furthermore, the discussion focuses on the application of the concept of ontology in the context of accounting science. It explains how ontology influences our understanding of the objects of accounting study, ranging from assets, liabilities, equity, to economic transactions. A deep understanding of ontology is expected to provide a strong basic framework for the development of more relevant and robust accounting theories and practices.